The sum of the first ten terms of an arithmetic progression is four times the sum of its first five terms. Find the ratio of the first term to the third term?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Let each term of this arithmetic series be represented by x + ( n − 1 ) y . We are given that:
Σ n = 1 1 0 x + ( n − 1 ) y = 4 [ Σ n = 1 5 x + ( n − 1 ) y ] ⇒ 1 0 x + 4 5 y = 4 ( 5 x + 1 0 y ) ⇒ y = 2 x .
If we desire the ratio of the first to the third term, then x + 2 y x = x + 2 ( 2 x ) x = 1 + 4 1 = 5 1 .